Penolakan Mahar Pecahan Nominal Sesuai Tanggal Tertentu Di KUA Kecamatan Bojonegoro Perspektif Hukum Islam - Fauziyah, Ririn; Hamdan, Ali; Khoir, Muhammad Abul (ASASI: Journal of Islamic Family Law, 2024)
Dowry is a mandatory gift from a man to a woman after performing a marriage contract. The determination of dowry is often based on symbolic aspects such as adjusting the dowry to a certain nominal fraction according to the wedding date or other dates that are considered sacred. This phenomenon triggered the Marriage Registrar at the Bojonegoro Religious Affairs Office to reject the dowry on the grounds that the dowry with a certain nominal fraction contained elements of waste and futility. This attracts researchers to study and study more deeply the analysis of Islamic law on the rejection of nominal fractional dowry according to a certain date at the Bojonegoro Religious Affairs Office (KUA). The results of this study show that the reason why the Marriage Registrar (VAT) of KUA Bojonegoro refused, is because in the dowry there is a nominal fraction that has no value and has no benefit so that it seems to be symbolic. In addition, how to get the nominal denomination money by buying and selling that contains elements of usury. In addition, the acquisition of the dowry is considered difficult. The refusal made can be punished as mubah (permissible) according to Islamic Law because in its practice in the dowry there are fractions that are not valuable and useful and contain riba so that they do not meet the valid conditions for dowry that have been explained in Islamic Law.